Nilai perusahaan berdasarkan struktur modal dan kinerja keuangan - Maymunatul, Novia; Dewi, Veni Soraya; Mranani, Muji (Universitas Muhammadiyah Magelang, 2024)
Progress in the business world is marked by competition between companies. This causes companies to compete in increasing company value. The aim of this research is to test and analyze capital structure, profitability and liquidity on company value which is supported by Signal Theory so that multiple linear regression analysis is appropriate to use. The research sample is garment and textile companies listed on the Indonesia Stock Exchange which fulfill purposive sampling with an observation period of 2018-2022. The research results found that capital structure and profitability have no effect on company value, but liquidity can increase company value. The implications of this research are expected to provide input to management in making capital structure management policies and strategies for increasing profitability and liquidity ratios which can increase company value.